Pathways to positive youth development in Malaysian undergraduate 1 co-curricular programs: a moderated mediation model of youth 2 voice and psychological hardiness - Nouri, Katayoun Mehdinezhad; Krauss, Steven E.; Ahrari, Seyedali; Ismail, Ismi Arif; Arshad, Mohd Mursyid (Frontiers Media, 2022)
Youth voice is gaining more attention globally as a core feature of program quality within positive youth development programs. Few studies have examined the relationship between youth voice and positive youth development in high power-distance cultures, however, where young people often face psychological barriers to exercising decision-making in their work with program adults. Research is needed on the psychological mechanisms that might help youth thrive within settings that are less structurally and psychologically supportive of youth voice. Drawing on bioecological systems and hardiness theories, this quantitative correlational study evaluates the moderating effect of psychological hardiness on the relationship between youth voice, the mediators of program safety and engagement, and the 6 C’s of positive youth development. A moderated mediation model was tested among 436 first-year undergraduate co-curricular program participants from public universities in Malaysia ( M = 21.192 years, SD = 1.191 years; 65.6% female). Youth voice positively predicted positive youth development; the relationship was partially mediated by program engagement, but not safety. The mediated pathway through program engagement was more predictive for hardier youth. By combining programmatic and individual psychological factors into the hypothesized model, this research identifies the potential importance of hardiness on the practice of youth voice for young adults in high power distance cultures. The findings highlight the need to identify other individual and programmatic factors that may contribute to the development of positive youth development in diverse cultural settings.